Analysis on the Governance Wealth of Republic of Indonesia Police Primary Cooperative of Magetan Resort in 2011-2015 - Prasetio, Vensia Adzania (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research aims to reveal the governance of Republic of Indonesia Police Primary Cooperative, Magetan Resort (Primkopol Polres Magetan) in 2011-2015 based on the Decree of Small Business and Cooperatives Minister of Indonesia Republic No. 14/Per/M.KUKM/XII/2009 comprising capital aspects, productive assets quality, management, efficiency, liquidity, self-reliance, and self-identity of cooperative.This is a descriptive quantitative research focusing on a case study at Primkopol Polres Magetan in 2011-2015. The data analysis was run by comparing the calculation result on the health level aspects based on the Decree of Small Business and Cooperatives Minister of Indonesia Republic No. 14/Per/M.KUKM/XII/2009.The result indicates that the health level of Primkopol Polres Magetan in 2011-2015 was quite healthy as the average score was 77.29. The score detail is as follow: (1) capital aspect average score was 15.00 categorized as healthy level; (2) productive asset quality aspect reached 23.70 average score which was categorized as healthy level; (3) management aspect attained average score of 12.96 categorized as healthy level; (4) efficiency aspect demonstrated an average score of 7.00 categorized as quite healthy level; (5) liquidity got 6.75 as its average score which was categorized as unhealthy level; (6) self-reliance and cooperative growth aspects demonstrated an average score of 6.40 categorized as quite healthy level; and (7) self-identity cooperative aspect reached 5.75 as its average score which was categorized as quite healthy level. Among the seven assessment items, capital and productive asset quality aspects were the best aspects compared to liquidity and cooperative self-identity aspects.Keywords: Health Level, Capital Aspect, Productive Asset Quality Aspect, Management Aspect, Efficiency Aspect, Self-Reliance and Cooperative Growth Aspect, and Self-Identity Aspect.